Nonlinear energy harvesting device for low frequency human motion application - Suhaimi, Khalis (2015)
Energy harvesting from ambient sources had received much attention in the past few years due to worldwide awareness on green technology expands. In vibration based energy harvesting, resonant linear generator are commonly used as the harvesting devices. However, a linear generator induces several limitations. The power harvested by a linear generator is proportional to the cube of excitation frequency and the power is maximum in a narrow bandwidth only. In this research, human motion vibration was selected as an input excitation and its frequency content is investigated. The frequency of human motion was investigated by placing a vibration recorder on a test subject under 5km/h walking and 9 km/h jogging speed.The investigation shows that the human motion vibration is distributed in the low frequency region. Hence, a device that can operate optimally with low frequency input and has the ability to overcome the narrow bandwidth limitation is designed. A device is designed to overcome the limitations of the linear generators. This device has the combination of the tuning, frequency-up conversion, multimodal and non-linear techniques. The aim is to amplify the input frequency to a higher frequency and at the same time, widen the bandwidth of response. The frequency-up mechanism is made by transforming the translation motion into the rotary motion by using gear ratio to amplify the response to a higher rotational speed. Winding springs are used with twistable enclosure cap to alter the device stiffness. The angles of twist of the enclosure cap are ranging from 180 degree to 900 degree. Two oscillating masses are connected to the device. Each mass can be set with different characteristic to widen the bandwidth. The two masses are also configured with non-linear softening and non-linear hardening properties to further widen the bandwidth. The non-linearities of the system are changed by varying the magnets gap. The non-linear restoring force of the system shows the influences of the linear coefficient and non-linear coefficient. The device is then investigated with two sets of experiments. The quasi-static measurement is to investigate the system stiffness and dynamic measurement is to investigate its response across a frequency range. In the dynamic measurement the device is excited with sinusoidal inputs and real human motion inputs. Overall, the results obtained from the experiment show that device is able to produce frequency amplification. The response also shows that with a properly tuned system, both softening and hardening can produce a flat response which is insensitive to excitation frequency as well as at amplified amplitude.